2007
DOI: 10.1002/prop.200610389
|View full text |Cite
|
Sign up to set email alerts
|

*‐Lie derivative, *‐covariant derivative and *‐gravity

Abstract: We construct functions and tensors on noncommutative spacetime by systematically twisting the corresponding commutative structures. The study of the deformed diffeomorphisms (and Poincaré) Lie algebra allows to construct a noncomutative theory of gravity.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Twisted deformations in this broader context are a step forward in the geometrization of the traditional Drinfeld scheme [35]. It has been argued in a seminal paper [18] (see also [13,39,54]) that such a framework is very useful in noncommutative geometry and deformed field theories and gives a hope to describe gravity at the Planck scale 1 .…”
Section: Preliminaries and Notationmentioning
confidence: 99%
“…Twisted deformations in this broader context are a step forward in the geometrization of the traditional Drinfeld scheme [35]. It has been argued in a seminal paper [18] (see also [13,39,54]) that such a framework is very useful in noncommutative geometry and deformed field theories and gives a hope to describe gravity at the Planck scale 1 .…”
Section: Preliminaries and Notationmentioning
confidence: 99%
“…Moreover, the theory is also invariant under the action of deformed diffeomorphisms. These are -deformations of infinitesimal diffeomorphisms, obtained by composing the Lie derivative with the twist [17,25]. The proof of the invariance of the action (2.74) under infinitesimal -diffeomorphisms is a straightforward generalization of the one given in [11,32] for the noncommutative Palatini action.…”
Section: Symmetries: Deformed Gauge Invariance and Dualitymentioning
confidence: 96%
“…In the following, we consider the full Palatini-Holst action, within the same geometric framework. The noncommutative structure is obtained via a twist-deformation of the differential geometry [17,25,26], which allows to build from first principles a modified theory of gravity having Planck scale modifications naturally built-in. There are two independent sources of new physical effects that may arise in such theories.…”
Section: Introductionmentioning
confidence: 99%
“…Namely, noncommutativity also affects the geometric or "pure" gravity side of the Einstein's equation. In numerous approaches [56][57][58][59][60][61][62][63] we have witnessed the NC corrections to Einstein's equation. Moreover, in [64][65][66] it has been indicated that the nature of the cosmological constant could be entirely noncommutative.…”
Section: Final Remarksmentioning
confidence: 99%